FAKTOR-FAKTOR YANG MEMPENGARUHI KONSUMEN TERHADAP KONSUMSI CABAI RAWIT DI KABUPATEN SEMARANG - Agung Sanjaya; Dewi Hastuti; Shofia Nur Awami (MEDIAGRO, 2017)
This study aims to determine the most preferred chili, to know an alternative substitution for cayenne chili and to analyzes the factors that affecting consumers on cayenne chili consumption in Semarang Regency. Location determination method using purposive sampling. Respondent sampling method was done by accidental sampling method. The location were Bandarjo Market, Babadan Market, Karangjati Market, Projo Market and Kembangsari Market in Semarang Regency. Total respondents were 50 people (10 respondents for each market). The analytical method that used are descriptive and multiple linear regression analysis. Based on the analysis, the most preferred chili in Semarang Regency is cayenne chili with the number 37 respondents (74 percent). The alternative subtitution for cayenne chili is keriting chili. The results showed that the coefficient of determination shown in the value of R Square of 0.719, which means that the consumption of cayenne chili  can be explained by the five independent variables in this research that age, price, income, level of preference and the number of family members of 71.9 percent and the rest is 28.1 percent can be explained by other variables outside the model in this research. Simultaneous testing (F-test) at a significance level (α) = 1 percent have significant value of 0.000 indicates that age, price, income, level of preference and the number of family members have significant effects on the consumption of chili. The results of t-test at a significance level (α) = 5 percent for the income variable with significant value 0,039 have significant effects partially on the consumption of chili. Price with significant level 0,002 and level of preference with significant value 0.000 at a significance level (α) = 1 percent have  significant effect partially on the consumption of cayenne chili in Semarang Regency. Keywords: Consumer, Consumtion, Cayenne Chili, Semarang Regency